Dependence of ohmic contact properties on AlGaN layer thickness for AlGaN/GaN high-electron-mobility transistors. (29th March 2016) - Takei, Yusuke; Tsutsui, Kazuo; Saito, Wataru; Kakushima, Kuniyuki; Wakabayashi, Hitoshi; Iwai, Hiroshi
Abstract: The dependence of ohmic contact resistance on the AlGaN layer thickness was evaluated for AlGaN/GaN high-electron-mobility transistor (HEMT) structures. Mo/Al/Ti contacts were formed on AlGaN layers with various thicknesses. The observed resistance characteristics are discussed on the basis of a model in which the overall contact resistance is composed of a series of three resistance components. Different dependences on the AlGaN layer thickness was observed after annealing at low temperatures (800–850 °C) and at high temperatures (900–950 °C). It was determined that lowering the resistance at the metal/AlGaN interface and that of the AlGaN layer is important for obtaining low-resistance ohmic contacts.